Economic Burden of Dental Diseases of Patients Attending the Dental Unit of University Hospital, Legon - Deh, S. K. (University of Ghana, 2015)
Introduction: Dental health is essential to the general well-being of an individual. The most common oral diseases are dental caries and periodontal diseases. Significant economic costs are incurred by dental patients however limited studies have been conducted on the economic burden dental diseases place on its patients. This study therefore aimed to, estimate the costs of dental diseases and determine the economic burden of dental diseases on patients. Methods: Cross-sectional design was used in this study. Data was collected from 185 patients attending the dental unit of University Hospital, Legon. Direct cost was estimated from medical and non-medical costs. Indirect cost was estimated by valuing productivity time lost to patients and intangible cost such as pain was described using the Likert scale. The socioeconomic differences in the cost of dental diseases were determined using the wealth quintiles of patients. Results: The estimated total cost of dental diseases was GHS 27,184.00 (US$ 6,614.11) with the direct cost constituting 94.5% and indirect cost constituting 5.5% of the total cost profile. The mean cost was GHS 146.94 (US$ 35.75). The richer socioeconomic group had the highest cost per quintile with a mean of GHS 191.89 (US$ 46.69). The intangible cost described was highest for pain (49.2%). Conclusion: The costs of dental diseases are enormous hence dental health services should be made affordable for patients. Oral health intervention programmes should focus more on preventive than curative care in order to prevent dental diseases with its associated health expenditure, productivity losses and intangible costs. Keywords: direct cost, indirect cost, intangible cost, socioeconomic status, dental diseases
Thesis (MPhil)- University of Ghana, 2015
Keywords: Dental health; Oral Diseases; Dental Caries; Periodontal Diseases